Analisis Stilistika Pada Puisi “Maqomat Cinta” Karya Heri Isnaini - Aini Ulwi Sifa (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
The study is intended to identify the use of figures of speech (majas), describing the words of heri isnaini's "love maqomat" poem. The source of data on this study is one of the poems of the heri isnaini poem called "light meditation," published in July 2017. This type of research involves qualitative methods. The theory used is that of sticism with the approach of sticism. The poem "maqomat of love" is analysed and discussed in a theological way to learn the implied meaning of the language heri isnaini through the application of style (majas), thus revealing the meaning of the poem "maqomat of love" clearly by the writer. This study of heri isnaini's maqomat love poem mentions that the language (majas) used is a form of retraction. The "reiteration" is a "pararism"; it is the "prescriptive" that describes something by repeating a word or a few words over and over again. A type of pararism applied to the poem "maqomat love" is anafora magician.